Resolution of single spin flips of a single proton - Mooser, Andreas; Kracke, H.; Blaum, Klaus; Bräuninger, S. A.; Franke, K.; Leiteritz, C.; Quint, Wolfgang; Rodegheri, C. C.; Ulmer, S.; Walz, J. (Physical review letters, 2013)
The spin magnetic moment of a single proton in a cryogenic Penning trap was coupled to the particle’s axial motion with a superimposed magnetic bottle. Jumps in the oscillation frequency indicate spin flips and were identified using a Bayesian analysis.